Combination of system biology and classical approaches for developing biorefinery relevant lignocellulolytic Rasamsonia emersonii strain. (May 2022) - Raheja, Yashika; Singh, Varinder; Kaur, Baljit; Basotra, Neha; Di Falco, Marcos; Tsang, Adrian; Singh Chadha, Bhupinder
Highlights: Classical and integrated system biology tools to develop hyper-cellulolytic strain. Comparative analysis of wild and developed strain at proteome and transcriptional level. Efficient hydrolysis of acid pre-treated rice straw slurry by developed enzyme. Spiking of developed enzyme with LPMO from M. thermophiloides from enhanced hydrolysis. Abstract: The objective of this study was to develop thermophilic fungus Rasamsonia emersonii using integrated system biology tools (genomics, proteomics and transcriptional analysis) in combination with classical strain breeding approaches. Developed hyper cellulolytic mutant strain M36 showed endoglucanase (476.35 U/ml), β-glucosidase (70.54 U/ml), cellobiohydrolase (15.17 U/ml), FPase (4.89 U/ml) and xylanase (485.21 U/ml) on cellulose/gram flour based production medium. Comparison of the expression profile at proteome and transcriptional level of the developed strain and wild type parent gave detailed insight into the up-regulation of different CAZymes including glycosyl hydrolases (GH5, GH6, GH7, GH3, GH10) and auxiliary enzymes (lytic polysaccharide monooxygenase, swollenin) at system level. Furthermore, the potential of lignocellulolytic enzyme produced by the developed strain and custom designed cocktail spiked with heterologously expressed lytic polysaccharide monooxygenase from Mycothermus thermophiloides were analyzed for the hydrolysis of biorefinery relevant unwashed pretreated rice straw slurry (PRAJ and IOCL) @17% substrate loading rate.